MORPHOMETRICAL ANALYSIS OF INTERVILLOUS SPACE AND VILLOUS MEMBRANE THICKNESS IN MATERNAL ANAEMIA - Kiran, Nazma; Zubair, Alia; Khalid, Henna; Zafar, Ambreen (Journal of Ayub Medical College Abbottabad, 2014)
Background: Anaemia in pregnancy is linked with an increased risk of preterm delivery, low birth weight, perinatal and maternal mortality and it is related with variable histo-morphological changes in placenta which show a reflection for the poor foetal outcome. The objective of this study is to assess the micro-morphometery of intervillous space and villous membrane of placenta in anaemic mothers. Methods: This case control study was carried out at Army Medical College, National University of Sciences and Technology Islamabad in collaboration with Department of Obstetrics and Gynaecology, Military Hospital, Rawalpindi, Pakistan, from December 2011 to November 2012. A total of 75 placentas were included, that were divided into study and control group. In control group (n=15) placentas were taken from mothers having normal haemoglobin levels and study group (n=60) included placentas from anaemic mothers having haemoglobin less than 11g/dl. Study group was subdivided into three groups, i.e., mildly (10.0-10.9g/dl), moderately (7.0-9.9g/dl) and severely (<7g/dl) anaemic group. Three representative sections were taken from placenta, i.e., one close to umbilical cord (A), one from periphery (C) and one midway between A and C (B).Ocular micro-meter was used to measure intervillous space and villous membrane thickness. Results: Intervillous space was prominent in study groups (41.26±16.33Ã¬m) as compared to control group (15.98±3.81Ã¬m) (p<0.05). Thickness of villous membrane was significantly less in study group as compared to control group (2.97±0.70) (p<0.05). Conclusion: The present study showed wide intervillous space and thin villous membrane in study group as compared to control group reflecting adaptive changes in response to hypoxiain maternal anaemia. Keywords: Intervillous space, villous membrane, maternal anaemia, Placenta